Ø§Ù‡Ù...ÙŠØ© Ø§Ù"Ø¬ÙˆØ§Ù†Ø¨ ÙÙ‰ ØªØ¹Ù"ÙŠÙ... Ø§Ù"ÙƒØªØ§Ø¨Ø© Ø§Ù"Ø¹Ø±Ø¨ÙŠØ© - Fajrul Hadi (Universitas Islam Negeri Ar-Raniry, 2014)
Arabic writing is the most difficult of language skills. There are many problems that will be faced by Arabic language learners in terms of writing special words form from right to the left. They must understand nahw and á¹£arf. A reader can not get a true information from the text if there is wrong writing. Hence there are grammars, steps and rules that must be known by Arabic language learners. In this article, the author also suggests some goals of learning Arabic. In the end, he writes some sorts of teaching writing skill, grammatical and application, vocabularies and application, and some Arabic writing styles. This study using library research by analyzing some books related for this discussion. Keywords: Instruction; Writing Skills; Arabic Language